PENGARUH SERVICESCAPE TERHADAP REVISIT INTENTION DENGAN PLEASURE FEELING EMOTION SEBAGAI VARIABEL MEDIASI (Studi Pada Pengunjung Wisata edukasi The Bagong Adventure Museum Tubuh) - Rahmat, Bagus Basuki (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to examine and analyze the influence of the implementation of servicescape against the revisit intention with the pleasure feeling emotion as a mediation variable ( A study at The Bagong Adventure Museum Tubuh). This explanatory research explains causal relation between the variables through hypothesis testing.This study uses 120 samples taken from the population of visitors of Wisata Edukasi The Bagong Adventure Museum Tubuh. The samples are selected using purposive sampling technique. The sample should be at least 17 years age, have visited Wisata Edukasi The Bagong Adventure Museum Tubuh at least once. Analysis Method using PLS SEM with SmartPLS software 3.2.6. The research instrument test includes test outer model, inner model test, and hypothesis test. The direct hypothesis test uses t-test while the hypothesis does not directly use the sobel test.The result of this study shows that, servicescape positively and significantly affect the pleasure feeling emotion of the visitors of Wisata Edukasi The Bagong Adventure Museum Tubuh. Pleasure feeling emotion does not have a positive and significant effect on the revisit intention of the visitor of Wisata Edukasi The Bagong Adventure Museum Tubuh. Servicescape positively and significantly affect the revisit intention of the visitors of Wisata Edukasi The Bagong Adventure Museum Tubuh. As for the indirect influence of servicescape to the revisit intention through the pleasure feeling emotion shows positive and significant results.KEYWORDS: Servicescape, Pleasure Feeling Emotion, Revisit Intention